Altered brain connectivity in Long Covid during cognitive exertion: a pilot study - Barnden, Leighton; Thapaliya, Kiran; Eaton-Fitch, Natalie; Barth, Markus; Marshall-Gradisnik, Sonya (Frontiers in Neuroscience, 2023)
Debilitating Long-Covid symptoms occur frequently after SARS-COVID-19 infection. Functional MRI was acquired in 10 Long Covid (LCov) and 13 healthy controls (HC) with a 7 Tesla scanner during a cognitive (color-word Stroop) task. BOLD time series were computed for 7 salience and 4 default-mode network hubs, 2 hippocampus and 7 brainstem regions (ROIs). Connectivity was characterised by the correlation coefficient between each pair of ROI BOLD time series. We tested for HC versus LCov differences in connectivity between each pair of the 20 regions (ROI-to-ROI) and between each ROI and the rest of the brain (ROI-to-voxel). For LCov, we also performed regressions of ROI-to-ROI connectivity with clinical scores. Two ROI-to-ROI connectivities differed between HC and LCov. Both involved the brainstem rostral medulla, one to the midbrain, one to a DM network hub. Both were stronger in LCov than HC. ROI-to-voxel analysis detected multiple other regions where LCov connectivity differed from HC located in all major lobes. Most, but not all, were weaker in LCov than HC. LCov connectivity was correlated with clinical scores for disability score and autonomic function and involve brainstem ROI. Multiple connectivity differences and correlations involved brainstem ROIs. Increased connectivity in LCov between the medulla and midbrain may reflect a compensatory response. This brainstem circuit regulates cortical arousal, autonomic function and the sleep-wake cycle. In contrast this circuit exhibited weaker connectivity in ME/CFS. LCov connectivity regressions with disability and autonomic scores confirm the consequences of altered brain connectivity in LCov.